PENGEMBANGAN WEBSITE BERBASIS GOOGLE SITES “SANADIQ“ TENTANG KISAH SAHABAT NABI ABU BAKAR ASH-SHIDDIQ PADA PEMBELAJARAN PAI KELAS V SD - Nur Aeni, Ani; Amelia, Rika; Sulistiawati; Widiyawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop and evaluate a website-based learning media called SANADIQ about the story of the Prophet's Companion Abu Bakar Ash-Shiddiq as an interactive educational tool in learning Islamic history. SANADIQ is designed with features that support the learning experience, such as interactive, quizzes, and interesting multimedia materials to support students' understanding and increase students' involvement in learning PAI class V elementary school. This research applies the D&D (Design & Development) method with the ADDIE development model through the stages of problem identification, objectives, design, development, trial and evaluation. The trial was conducted on 27 fifth grade students of SDN Rancapurut by involving media experts and material experts as validators. The evaluation results showed a very good assessment from users and validators. Although there are obstacles such as lack of facilities, namely limited classrooms and the busy activities of students. However, students remain active and happy to use this interactive learning media. The SANADIQ website is proven to increase learning motivation and encourage students to be actively involved during the learning process, and create fun learning. Teacher recommendations are to improve skills in technology to create innovative learning. This research can inspire other researchers to develop digital learning media innovations.